Administering higher education policies in the Baltic states: balancing the language demands in multilingual society. Issue 9 (21st October 2018) - Tamtik, Merli; Jang, Soon Young
ABSTRACT: Along with increased international migration, many nation-states are facing the dilemma of embracing a multi-cultural and multi-lingual society while protecting their cultural and linguistic heritage. Non-Anglophone universities are often the sites of this struggle as they aim to become world-class international universities operating largely in English, yet strive to reinforce national identities through language policies. This paper examines higher education policies vis-à-vis language in the Baltic states (Estonia, Latvia, and Lithuania). The aim of the paper is to identify how universities have positioned themselves to respond to the complexity of local, national, and global pressures regarding the use of national language versus other languages. Glonacal agency heuristic [Marginson and Rhoades 2002, 'Beyond National States, Markets, and Systems of Higher Education: A Glonacal Agency Heuristic.' Higher Education 43 (3): 281–309] was used to frame the study. Content analysis of 16 policy documents revealed that while the practices might still lean towards English as the dominant foreign language in the higher education context, there are distinct strategic steps taken in the institutional and national contexts to support maintaining cultural and linguistic diversity in the Baltic States.